Pronouns as Power: A Tripartite Linguistic Inquiry into Referent Erasure, Political Distance, and Deixis in Students’ English Debates - Margaret Stevani; Evi Martiningsih; Tiara Panduwinata; Loso Judijanto; Rinovian Rais; Suroso (SALEE: Study of Applied Linguistics and English Education, 2026)
This study investigated the ideological functions of pronouns in Indonesian EFL student political debates through a tripartite analytical framework consisting of referent erasure, political distance, and deixis. Grounded in Critical Discourse Analysis, the research examined how pronoun choices functioned not only as grammatical references but also as rhetorical strategies for negotiating power, alignment, and agency. The data were collected from 26 undergraduate students from Universitas Pembinaan Masyarakat Indonesia, Politeknik Angkatan Laut, and Institut Keislaman Tuah Negeri during six real-time English debate sessions conducted in 2026. Debate transcripts were analyzed qualitatively to identify patterns in the use of pronouns such as we, they, you, and impersonal constructions. The findings revealed that students strategically shifted pronoun usage to construct solidarity, distance opposing groups, obscure responsibility, and strengthen persuasive arguments within civic and political discussions. Pronouns thus operated as micro-sites of ideological negotiation that reflected identity positioning and contextual meaning-making. This study contributed to applied linguistics and English language education by demonstrating how EFL learners used grammatical forms to exercise voice, persuasion, and ideological stance in multilingual academic discourse.